1985
DOI: 10.1113/jphysiol.1985.sp015758
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular analysis of gamma‐aminobutyric‐acid‐associated ion movements in rat sympathetic neurones.

Abstract: SUMMARY1. Double-barfelled ion-sensitive micro-electrodes were used to measure the changes of the intracellular activities of Cl-, K+, and Na+ (at1, ak, aka) in neurons of isolated rat sympathetic ganglia during the action of y-aminobutyric acid (GABA).2. The membrane potential of some of the neurones was manually 'voltage clamped' by passing current through the reference barrel of the ion-sensitive micro-electrode. This enabled us to convert the normal depolarizing action of GABA into a hyperpolarization.3. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 40 publications
(59 reference statements)
7
66
0
Order By: Relevance
“…Similar values were estimated with noninvasive microfluorimetric methods (Shimizu- Ikeda et al, 2003;Zhang et al, 2006 (Rohrbough and Spitzer, 1996;Payne et al, 2003). One possible mechanism for active Cl Ϫ accumulation in neurons is Na ϩ -and K ϩ -dependent Cl Ϫ uptake (Ballanyi and Grafe, 1985;Alvarez-Leefmans et al, 1988). Such uptake can be mediated by the Na ϩ -K ϩ -2Cl Ϫ -cotransporter, a member of the cation-chloride-cotransporter family that uses the Na ϩ gradient for active Cl Ϫ accumulation and can be inhibited by loop diuretics like bumetanide (Delpire, 2000;Russell, 2000).…”
supporting
confidence: 55%
“…Similar values were estimated with noninvasive microfluorimetric methods (Shimizu- Ikeda et al, 2003;Zhang et al, 2006 (Rohrbough and Spitzer, 1996;Payne et al, 2003). One possible mechanism for active Cl Ϫ accumulation in neurons is Na ϩ -and K ϩ -dependent Cl Ϫ uptake (Ballanyi and Grafe, 1985;Alvarez-Leefmans et al, 1988). Such uptake can be mediated by the Na ϩ -K ϩ -2Cl Ϫ -cotransporter, a member of the cation-chloride-cotransporter family that uses the Na ϩ gradient for active Cl Ϫ accumulation and can be inhibited by loop diuretics like bumetanide (Delpire, 2000;Russell, 2000).…”
supporting
confidence: 55%
“…One approach is to measure the intracellular chloride activity directly by means of Cl--selective microelectrodes. Measurements of this kind have, indeed, shown that Cl-ions are actively accumulated in rat sympathetic neurones (Ballanyi & Grafe, 1985) and in amphibian dorsal root ganglion cells (AlvarezLeefmans, Gamiiio, Giraldez & Nogueron, 1988), which is compatible with the depolarizing action of GABA observed in these cells. However, an accurate measurement of the steady-state level of postsynaptic a', by means of Cl--selective electrodes is hampered by various technical problems including interference by GABA-GATED BICARBONATE CONDUCTANCE intracellular anions other than Cl-and differences in the value of the membrane potential as sensed by the ion-selective microelectrode and its reference electrode (cf.…”
Section: Gaba-gated Bicarbonate Conductancementioning
confidence: 63%
“…A more promising approach is to examine whether the direction of the electrogenic Cl-flux mediated by postsynaptic anion channels is compatible with the effects of the transmitter on membrane potential (see Fig. 4, and Neild & Thomas, 1974;Ballanyi & Grafe, 1985). Nevertheless, we feel that with present electrode techniques, the most reliable way to obtain a direct estimate of E01 is to measure the reversal potential (EJ,) of instantaneous, channel-mediated Cl-fluxes (cf.…”
Section: Gaba-gated Bicarbonate Conductancementioning
confidence: 99%
“…It is possible that the M-current is involved in the depolarizing component of responses to ATP and ,P-MeATP but it seems unlikely that it is involved in the effect of adenosine and 1,y-MeATP in augmenting GABA-induced depolarizations. The effect of GABA on the rat SCG involves an increase in efflux of K+ and chloride ions (Ballanyi & Grafe, 1985). Therefore the ability of adenosine and P,y-MeATP to increase depolarization caused by GABA in the SCG may involve augmentation of the increased chloride efflux as reported by Ferrero & Frischknecht (1983) on guinea-pig taenia coli, or may be due to a change in the GABA-receptor/ion channel complex as described for bullfrog sensory ganglia by Morita et al (1984).…”
Section: Effect Ofpurines On the Gaba-induced Depolarizationmentioning
confidence: 82%